90.4k views
25 votes
7(2 + 6 – 4d) = pl help me I don’t get it

7(2 + 6 – 4d) = pl help me I don’t get it-example-1
User Freestate
by
4.8k points

2 Answers

11 votes

Answer:

7(2 + 6 - 4d) = 7(8 - 4d) = (56 - 28d)

Explanation:

There is no possible answer to this equation but this is the most accurate equation, since you cant go any further, this is your simplified form.

User Jaxoncreed
by
6.1k points
9 votes

Answer:

Explanation:

1. 1 Simplify 2+6-4d to -4d+8.

7 ( -4d + 8)

therefor, the answer is, 7( -4d + 8)

User Dcharles
by
5.5k points